Indole-3-Butyric Acid Enhances Root Formation and Alleviates Low-Temperature Stress in Sugarcane: Molecular Insights and Identification of Candidate Genes - Xiao-Qiu Zhang; Yong-Jian Liang; Xiu-Peng Song; Mei-Xin Yan; Li-Qiu Tang; Zhen-Qiang Qin; Yu-Xin Huang; De-Wei Li; Dong-Mei Huang; Ze-Sheng Shi; Bao-Qing Zhang; Dong-Liang Huang (Plants)
Sugarcane (Saccharum officinarum L.) faces significant challenges in China, including labor-intensive cultivation, low yields, and environmental stresses. Enhancing root development and stress tolerance through phytohormones and molecular breeding is a promising approach to boosting productivity. Indole-3-butyric acid is a phytohormone known for promoting root development and stress resistance. However, its effects on sugarcane root development under low temperature remain poorly understood. This study demonstrated that IBA markedly promoted root initiation, elongation, and biomass under low temperature, and significantly increased the levels of phytohormones, including GA3, ABA, JA, IAA, and ZT, suggesting the activation of multiple signaling pathways. Transcriptome analysis revealed numerous differentially expressed genes related to metabolic pathways such as glycolysis, the tricarboxylic acid cycle, and glutathione metabolism. Weighted gene co-expression network analysis identified core gene modules correlated with phytohormone activities, highlighting their role in the IBA-mediated stress response. Eleven core genes, including GSTU6, FAR1, and BCAT3, and nine hub genes, such as Ub-CEP52-1 and ACS1, were identified as critical components for IBA-induced root development and stress mitigation. These findings provide insights into the molecular mechanisms underlying IBA-induced root development and stress tolerance in sugarcane, offering candidate genes for breeding high-yield, stress-tolerant varieties and demonstrating IBA’s potential as a strategy to enhance productivity under challenging conditions.